2017
DOI: 10.1073/pnas.1716981114
|View full text |Cite
|
Sign up to set email alerts
|

Robust zero resistance in a superconducting high-entropy alloy at pressures up to 190 GPa

Abstract: SignificanceHigh-entropy alloys (HEAs) are made from multiple transition-metal elements in equimolar or near-equimolar ratios. The elements in HEAs arrange themselves randomly on the crystallographic positions of a simple lattice. In addition to their excellent mechanical properties, one HEA has been reported to display superconductivity. In this work, we report that the Ta–Nb–Hf–Zr–Ti high-entropy alloy superconductor exhibits extraordinarily robust zero-resistance superconductivity under pressure up to 190.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 152 publications
(78 citation statements)
references
References 37 publications
(55 reference statements)
7
61
0
Order By: Relevance
“…An excellent additional test of our theoretical results would be a measurement of the electronic heat capacity under pressure, which would allow verification of the observed decrease in both N (E F ) and λ. Calculated pressure dependence of Tc of (TaNb)0.67(HfZrTi)0.33 for two constant values of µ * = 0.13 and µ * = 0.215, variable µ * (P ) (see, Fig 15) and compared to experiment [6]. The electron-phonon coupling constant λ is defined as:…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An excellent additional test of our theoretical results would be a measurement of the electronic heat capacity under pressure, which would allow verification of the observed decrease in both N (E F ) and λ. Calculated pressure dependence of Tc of (TaNb)0.67(HfZrTi)0.33 for two constant values of µ * = 0.13 and µ * = 0.215, variable µ * (P ) (see, Fig 15) and compared to experiment [6]. The electron-phonon coupling constant λ is defined as:…”
Section: Discussionmentioning
confidence: 99%
“…Here, the same approach is applied to (TaNb) 0.67 (HfZrTi) 0.33 system to study evolution of superconducting properties under pressure. As far as the crystal structure is concerned, high pressure synchrotron X-ray diffraction measurements were performed in the pressure range from 0 to 96 GPa and it was shown that (TaNb) 0.67 (HfZrTi) 0.33 maintains the bcc structure, since no structural distortion was observed [6]. As there is no information on the crystal structure above this pressure we limit our studies to the pressure range from 0 to 100 GPa.…”
Section: Electronic Structurementioning
confidence: 99%
See 3 more Smart Citations